2020
DOI: 10.4132/jptm.2020.06.01
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of <i>TP53</i> mutations by p53 immunohistochemistry and their prognostic significance in gastric cancer

Abstract: Background: Recently, molecular classifications of gastric cancer (GC) have been proposed that include TP53 mutations and their functional activity. We aimed to demonstrate the correlation between p53 immunohistochemistry (IHC) and TP53 mutations as well as their clinicopathological significance in GC. Methods: Deep targeted sequencing was performed using surgical or biopsy specimens from 120 patients with GC. IHC for p53 was performed and interpreted as strong, weak, or negative expression. In 18 cases (15.0%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 29 publications
6
30
0
1
Order By: Relevance
“…For the statistical analysis, p53 IHC staining was interpreted in two tiers: strong nuclear staining in more than 10% of tumor cells was considered as overexpression positive, samples without any nuclear staining of tumor cells (complete absence) or cases exhibiting weak, scattered, or patchy positivity were interpreted as overexpression negative (Fig. 1) [21]. Accuracy of inter/ intra-observer concordance for p53 positivity is very high 1 3 with the following reasons: (1) Most cases were diagnosed by prof. HSL alone, (2) The other cases were diagnosed after sharing the diagnosis criteria with Prof. Lee's.…”
Section: Immunohistochemical Studymentioning
confidence: 99%
See 2 more Smart Citations
“…For the statistical analysis, p53 IHC staining was interpreted in two tiers: strong nuclear staining in more than 10% of tumor cells was considered as overexpression positive, samples without any nuclear staining of tumor cells (complete absence) or cases exhibiting weak, scattered, or patchy positivity were interpreted as overexpression negative (Fig. 1) [21]. Accuracy of inter/ intra-observer concordance for p53 positivity is very high 1 3 with the following reasons: (1) Most cases were diagnosed by prof. HSL alone, (2) The other cases were diagnosed after sharing the diagnosis criteria with Prof. Lee's.…”
Section: Immunohistochemical Studymentioning
confidence: 99%
“…Immunostaining of p53 is strongly associated with missense mutation; of the 12 missense mutations, 10 cases (83.3%) were positive for p53 immunostaining, but not with frameshift or nonsense mutations in TP53 [42]. However, according to a recent study of Hwang et al, strong p53 expression could predict nonsynonymous missense mutations with a sensitivity of 90.9%, specificity of 95.4%, and accuracy of 94.2% [21]. Furthermore, p53 overexpression and nonsynonymous TP53 mutations correlate with lower survival compared with other mutations.…”
Section: Multivariate Analyses Revealed P53 Overexpression Was Anmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some cases but not all cases that had p53 mutant pattern IHC had mutation pattern on IHC was not consistent with all mutations on TP53 sequencing, all wild0type pattern did not have significant TP53 mutation in sequencing (S1 Table ). In addition, there has been studies that correlated the mutation status of TP53 and p53 IHC [26,45]. However, other confirmative method such as Sanger sequencing would have promised more accurate data and results.…”
Section: Plos Onementioning
confidence: 99%
“…It has been reported that mutations of the p53 gene or other components of p53-pathway (e. g. Mdm2 and Mdmx) are detected in almost all cancer patients [8][9][10][11][12]. Prognostic value of p53 gene expression in gastric cancer has been intensively studied [13,14]. However, some studies suggest that patients with low p53 expression tends to have better survival outcome, while other studies show that p53 expression has no relation with survival outcome [15,16].…”
Section: Introductionmentioning
confidence: 99%